Relationship between Family Harmony and Juvenile Delinquency in Jorong Koto Ronah Nagari Koto Alam, Lima Puluh Kota - Higa Afrizal Putri; Setiawati Setiawati; Jalius Jalius (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2019)
This research is motivated by the high level of juvenile delinquency in Jorong Koto Ronah Nagari Koto Alam Subdistrict of Pangkalan, Lima Puluh Kota District. The author suspects the cause is due to lack of family harmony. Therefore this study aims to describe family harmony, describe juvenile delinquency and see the relationship between family harmony with juvenile delinquency in Jorong Koto Ronah Nagari Koto Alam Subdistrict of Pangkalan, Lima Puluh Kota District. This research is a quantitative research with correlational type. The population was all 41 male teenagers with a total sample of 31 people. The sampling technique is done by simple random sampling. Data collection techniques used in this study were questionnaires with questionnaire data collection tools. Data analysis techniques using the percentage formula and product moment. The results showed that (1) family harmony in Jorong Koto Ronah can be classified in the category of less harmonious, (2) the level of juvenile delinquency can be classified in the naughty category (3) there is a significant negative correlation between family harmony with juvenile delinquency Suggestions that the author can giving is expected to adolescent parents to maintain, improve family harmony, and supervise children so as not to do mischief, It is expected that all teenagers in Jorong Koto Ronah can be more careful of negative relationships outside the family environment, so they can avoid form juvenile delinquency, it is hoped that future researchers will be able to see several other factors which have not been examined in this study.Keywords: Family Harmony, Juvenile Delinquency